2017
DOI: 10.1186/s12966-017-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Which physical and social environmental factors are most important for adolescents’ cycling for transport? An experimental study using manipulated photographs

Abstract: BackgroundEcological models emphasize that cycling for transport is determined by an interplay between individual, physical and social environmental factors. The current study investigated (a) which physical and social environmental factors determine adolescents’ preferences towards cycling for transport and (b) which individual, physical and social environmental factors are associated with their intention to actually cycle for transport.MethodsAn online questionnaire consisting of questions on individual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…In line with previous studies [ 12 14 ], the present study showed that a short cycling distance is one of the most important factors determining the route choice of adolescent cyclists, as for 73.1% of the cycling trips participants took the shortest possible route. In addition, for 35.1% of the cycling trips which were not the shortest possible, adolescents still indicated that they chose that route because they perceived it as the shortest/fastest route.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies [ 12 14 ], the present study showed that a short cycling distance is one of the most important factors determining the route choice of adolescent cyclists, as for 73.1% of the cycling trips participants took the shortest possible route. In addition, for 35.1% of the cycling trips which were not the shortest possible, adolescents still indicated that they chose that route because they perceived it as the shortest/fastest route.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the evaluation of physical environmental characteristics along adolescents’ actual cycling routes remains understudied, although it is important to find out why individuals chose a specific cycling route. In addition, although previous studies emphasized the importance of distance for adolescents’ cycling for transport [ 12 14 ], it is likely that adolescents do not always take the shortest cycling route. By comparing adolescents’ actual cycling routes with the shortest possible cycling routes, important information regarding which physical environmental characteristics determine the route choice of adolescent cyclists may be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of interventions to increase active school transport vary and the quality of evidence remains low [59]. Well-separated and safe cycling infrastructure seems to be more important to adolescents than distance and the social environment [60]. We can also expect more health benefits in adolescents who cycle than in non-cyclists [9].…”
Section: The Association Between Active Travel and Well-beingmentioning
confidence: 99%
“…The cyclist preferred to do cycling is based on their high preferences about the overall environment that suit their specification needed. To measure the environmental preferences is categorised into four attributes, for instance, speed, space, security and distance that influence the cycling participation [32], [33]- [35].…”
Section: The Perceived Physical Environment and Cycling Participationmentioning
confidence: 99%
“…Besides, coherence, directness, attractiveness, traffic safety, comfort, and spatial integration are the proper design for cycle-network [37]. Repercussions, four aspects of bikeway design factors will be measured in the study such as safety/security (SSF) [33], [38]- [40], accessibility/connectivity (ACF) [38], [41], [42], attractiveness/aesthetic (AAF)…”
Section: Cycling-friendly Neighbourhood Factor For the Convenience Cymentioning
confidence: 99%